VIII. Perception of Document Management Systems in Digital Transformation - Jordan, Sandra; Bobek, Samo; Sternad Zabukovšek, Simona (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
Document Management Systems (DMS) are essential tools for managing organisational information throughout its lifecycle. Despite increasing adoption, many DMS implementations fail to deliver the expected value due to inadequate attention to Critical Success Factors (CSFs). This monograph investigates the impact of selected CSFs—such as top management support, process orientation, and organisational culture—on different phases of the DMS lifecycle: selection, implementation, and usage. Drawing on the ITIL framework and lifecycle-based thinking, the study employs a quantitative methodology using PLS-SEM on data collected from Slovenian organisations. The results show that CSFs vary in importance across lifecycle stages, highlighting the need for dynamic, phase-specific implementation strategies. The findings contribute to theory by integrating CSFs with DMS lifecycle management and provide actionable insights for practitioners seeking to optimise DMS adoption and performance.